Platelet activation during exercise induced asthma: effect of prophylaxis with cromoglycate and salbutamol. Issue 4 (April 1986) - Johnson, C E; Belfield, P W; Davis, S; Cooke, N J; Spencer, A; Davies, J A
Abstract : Peak expiratory flow (PEF) and plasma concentrations of platelet factor 4 and beta thromboglobulin were measured before and after exercise in nine asthmatic patients and 12 non-asthmatic volunteers. Exercise was preceded by administration in random order of either placebo, salbutamol 200 micrograms, or sodium cromoglycate 2 mg from a pressurised inhaler. In control subjects there were minimal changes in PEF and plasma concentrations of platelet factor 4 and beta thromboglobulin. In the asthmatic patients the typical changes in PEF were seen on exercise; plasma concentrations of platelet factor 4 and beta thromboglobulin rose significantly in parallel, the rise preceding the fall in PEF. The changes in peak flow and platelet activation induced by exercise were attenuated by prior administration of salbutamol or cromoglycate. These results indicate that exercise induced asthma is associated with a rise in platelet release products similar to that observed in antigen induced asthma.